A Theoretical Framework of Developing Leadership Capacity for Successful Organizational Outcomes - Markova, Mariya; Taysever, Guray; Angelov, Slav (Universitas Gadjah Mada, 2024)
Introduction/Main Objectives: To identify the effect of developing leadership capacity and focusing on the benefits of training and coaching individuals and teams in organizations. Background Problems: In this research, the authors examined the development of leadership capacity and its components, such as teamwork, motivation, leadership skills and the benefits of training and coaching for success in organizational outcomes. Novelty: Developing leadership capacity helps organizations achieve success and their strategic goals through coaching and training and the acquisition of new knowledge and skills. Research Methods: Empirical research was designed to gather data on the subject of the study. The authors added an extensive description of the data retrieved, which summarized their research on the topic. A theoretical framework was established to examine the link between developing leadership capacity and an organization’s performance. Finding/Results: The theoretical framework suggests that there is a strong statistically significant relationship between leadership capacity, skills, teamwork, training, and coaching influencing teamwork and motivation, which brings successful organizational outcomes. The authors found that involving training and coaching at workplaces had positive effects on individuals and teams. Conclusion: Authors discuss and provide a research agenda that might transform the field of leadership in organizations.